Building Capacity for the U.S. Mineral Resources Workforce: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
The extraction of mineral resources provides the raw materials necessary to produce the products and technologies on which the global economy depends, including green technologies essential for decarbonization. Mineral extraction requires expertise in a range of areas - including mineral resources identification, environmental evaluation, processing, and reclamation - but many of the U.S. academic programs that have historically educated the U.S. minerals workforce face significant challenges attracting students and maintaining financial viability. For some programs, enrollment dropped 60 percent from 2015 to 2023, despite a growing demand for a minerals workforce. The National Academies convened a workshop on January 23-24, 2024 to consider how the United States can build the capacity of federal and state agencies, academia, and the private sector to meet U.S. mineral workforce needs. Participants addressed the urgent need to attract more students, discussed a need to integrate new disciplines into curricula as the industry evolves, and identified multipronged approaches to help enhance overall retention and recruitment. This proceedings synthesizes the key suggestions presented by participants that universities, companies, and government agencies could take to enhance the recruitment, training, and retention of workers in the mineral resources industry.

Progress and Priorities in Ocean Drilling: In Search of Earth's Past and Future - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Research supported by scientific ocean drilling has fundamentally transformed our understanding of the planet with key contributions to the discovery and theory of plate tectonics; the formation and destruction of ocean crust; the reconstruction of extreme greenhouse and icehouse climates; the identification of major extinctions; and the discovery of a diverse community of microbes living deep ocean seafloor. With the retirement in 2024 of the JOIDES Resolution– the U.S. dedicated drilling vessel for deep sea research and the workhorse for the international scientific ocean drilling community– the scientific ocean drilling landscape will change. At this critical juncture, the National Science Foundation (NSF) is looking to identify the most urgent research questions that can only be answered with scientific ocean drilling and what infrastructure is needed to progress those priorities. This interim report that is the first part of a broader study of decadal survey of ocean science provides a broad perspective of future research and associated infrastructure needs. The report concludes that the rapid pace of climate change, related extreme events, sea level rise, changes in ocean currents, chemistry threatening ocean ecosystems, and devastating natural hazards are among the greatest challenges facing society. By coring the past to inform the future, U.S. based scientific ocean drilling research continues to have unique and essential roles in addressing these vital and urgent challenges.

Seismic Site Response Analysis with Pore Water Pressure Generation: Resources for Evaluation - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
There are many seismic site response analysis programs that operate in either the time domain or the frequency domain. These programs are available as public domain software, as commercial products, and\/or through direct contact with the authors. NCHRP Web-Only Document 383: Seismic Site Response Analysis with Pore Water Pressure Generation: Resources for Evaluation, from TRB's National Cooperative Highway Research Program, is supplemental to NCHRP Research Report 1092: Seismic Site Response Analysis with Pore Water Pressure Generation: Guidelines. Supplemental to the document is an Implementation Plan.

Future Directions for Southern Ocean and Antarctic Nearshore and Coastal Research - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Antarctica hosts some of the harshest and most remote environments on Earth - and it is a region of vital importance for scientific research. The environment and position of Antarctica on the globe mean that research conducted there can offer unique insights on important Earth processes, including rising sea level, the carbon cycle, ecosystem structure. As the climate warms, data gathered from Antarctic research will be essential to understanding how Earth processes are changing and the potential social, economic, and health impacts on both U.S. and global populations. This report identifies the highest priorities for research in the Southern Ocean and nearshore and coastal Antarctica, as well as gaps in current capabilities to support this research. Global sea level rise, heat and carbon budgets, and changing ecosystems are the three highest-priority science drivers for research in the region. To address those drivers and maintain a robust U.S. research presence in this vitally important region, investments are needed in the U.S. Antarctic program and its research platforms, including the development of new technologies and the replacement of aging icebreaking research vessels. Additionally, the U.S. should strengthen relationships with other nations2019 Antarctic programs that can help support these essential science drivers.

Prevention and Mitigation of Surficial Slope Failures on Fill Highway Embankment Slopes - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Surficial slope failures in highway fill embankments are shallow landslides that occur within the embankment fill, usually affecting only a portion of the slope2019s height. These failures tend to occur after a vulnerable embankment slope is subjected to a triggering event. An embankment2019s failure susceptibility generally depends on factors such as slope steepness, material composition, and ability to withstand adverse drainage conditions. Examples of trigger mechanisms include intense rainfall, snowmelt, seismic activity, and reshaping of the embankment. NCHRP Synthesis 617: Prevention and Mitigation of Surficial Slope Failures on Fill Highway Embankment Slopes, from TRB's National Cooperative Highway Research Program, documents state departments of transportation practices on identification, investigation, design guidance and requirements, prevention, and mitigation of surficial slope failures.

Seismic Site Response Analysis with Pore Water Pressure Generation: Guidelines - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
One-dimensional (1D) equivalent-linear total-stress site response analysis (SRA) is the de facto standard for state department of transportation (DOT) highway facilities at locations where site-specific ground response analyses are conducted. However, many users and various DOTs have concerns about the applicability of equivalent-linear analyses for the cases where site-specific SRA is most relevant. NCHRP Research Report 1092: Seismic Site Response Analysis with Pore Water Pressure Generation: Guidelines, from TRB's National Cooperative Highway Research Program, presents guidelines for the selection and use of methods for 1D nonlinear seismic SRA with excess pore water pressure generation and dissipation. Supplemental to the report is NCHRP Web-Only Document 383: Seismic Site Response Analysis with Pore Water Pressure Generation: Resources for Evaluation.

AI for Scientific Discovery: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Over the past century, artificial intelligence (AI) has evolved from computational theory to everyday conversational technologies, capturing the attention and interest of the public and the media. It has also caught the attention of the scientific community, where it has provided a new tool to support inquiry and exploration. While AI in the context of scientific investigation has existed for decades, advances in computational technology and sensing in the physical world have created opportunities to integrate AI into science in unexpected ways, with capabilities that are rapidly accelerating. As a result, AI has been leveraged by an expanding collection of disciplines in the physical and biological sciences, as well as engineering domains. While the opportunities for AI in scientific discovery seem endless, there are numerous questions about what makes for trustworthy and reliable discovery, whether such investigation should be performed without human oversight or intervention, and how best to prioritize the research agenda and allocation of resources without magnifying disparities for individuals and nations alike. In recognition of the timeliness and sizable implications of AI in our world, the National Academies of Sciences, Engineering, and Medicine hosted AI for Scientific Discovery - A Workshop on October 12-23, 2023. Leaders from across the globe in the field of AI, preeminent researchers in various science and engineering disciplines, and experts in ethics, law, and social sciences met to appraise the state of the field and provide guidance on the opportunities, as well as the challenges, that lay ahead. Presentations and discussion explored the future of AI in terms of its role as an autonomous researcher carrying out discovery and considered ethical aspects of AI used for independent scientific discovery.

Truck Emergency Escape Ramp Design and Operation - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Many state departments of transportation (DOTs) build and operate escape ramps to allow heavy trucks that cannot maintain safe speeds on steep downgrades to safely exit the highway instead of losing control and crashing. Some escape ramps use upward-sloping beds of loose aggregate to slow the vehicles, while others employ passive or active mechanical devices such as cables to slow the vehicles. Some agencies use intelligent transportation technologies to detect trucks that are driving at excessive speeds for the location and to provide information to truckers regarding emergency escape ramp locations. NCHRP Synthesis 621: Truck Emergency Escape Ramp Design and Operation, from TRB's National Cooperative Highway Research Program, documents practices used by state DOTs to design and operate facilities to detect, guide, and capture out-of-control vehicles travelling on steep downgrades.

Supporting Family Caregivers in STEMM: A Call to Action - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Family caregiving is not simply an outside obligation that has no bearing on the workings of academic science, technology, engineering, mathematics, and medicine (STEMM) as it affects the lives of so many people working and studying in colleges and universities around the country. Caregiving responsibilities often clash with ingrained norms in academic STEMM environments, which demand that STEMM students and workers demonstrate immense devotion to their fields and are always available and visibly working. Supporting Family Caregivers in STEMM describes the ways in which the labor and contributions of caregivers are often invisible and undervalued, with a specific focus on the academic STEMM ecosystem, including undergraduate and graduate students, postdoctoral scholars, resident physicians and other trainees, tenure-track and non-tenure-track faculty, staff, and researchers. This report reviews policies and practices that support caregivers, locally and nationally, and describes best practices in policy implementation and design. Supporting Family Caregivers in STEMM also highlights innovative practices and offers actionable recommendations to higher education institutions, public and private funders, and the federal government.

Selection and Application of Manning’s Roughness Values in Two-Dimensional Hydraulic Models - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Measures to improve the accuracy, reliability, and consistency in selecting roughness values for the application of 2D hydraulic models at highway crossings and in transportation corridors will represent a major step forward in the evolving state of practice. Whether a one-dimensional or a 2D modeling approach is taken, inconsistencies can exist from state to state, and even within states at the various district levels, on how to develop accurate and reliable hydraulic models. The fundamental issue is the selection and assignment of Manning2019s roughness values for a variety of channel types and land uses. NCHRP Research Report 1077: Selection and Application of Manning2019s Roughness Values in Two-Dimensional Hydraulic Models, from TRB's National Cooperative Highway Research Program, presents guidelines for the selection and application of Manning2019s roughness values for 2D hydraulic models.

Building Defense Research Capacity at Historically Black Colleges and Universities, Tribal Colleges and Universities, and Minority-Serving Institutions: Proceedings of Three Town Halls - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
A planning committee of the National Academies of Sciences, Engineering, and Medicine convened a series of three hybrid workshops to examine the key issues highlighted in the National Academies 2022 consensus study report, Defense Research Capacity at Historically Black Colleges and Universities and Other Minority Institutions: Transitioning from Good Intentions to Measurable Outcomes. As Department of Defense and other partners sought to implement the 2022 report recommendations, key questions remained to be explored, particularly related to how to seek ways of building research capacity at minority institutions (MIs) and develop true partnerships between MIs, other institutions of higher education, and federal agencies. The workshops featured commissioned research and literature reviews as well as case studies to illuminate problems, barriers, and approaches to increase research capacity at Historically Black Colleges and Universities.

Business Intelligence Techniques for Transportation Agency Decision-Making (The National Academies Press, 2024)
Strategic approaches to the management and operation of transportation systems blend knowledge of agency goals, asset conditions, traffic and safety performance, and finance and budget constraints. This knowledge is based on data, and many agencies are implementing consolidated data governance practices to improve data quality, maximize the value of the data to the agency, and better manage data collection and analysis resources. NCHRP Research Report 1099: Business Intelligence Techniques for Transportation Agency Decision-Making, from TRB's National Cooperative Highway Research Program, presents a state-of-the-art guide cataloging new techniques to extract actionable information from traditional and new data sources to enhance decision-making processes. Supplemental to the report are Business Intelligence Techniques for Transportation Agency Decision Making: Implementation Plan and Research Recommendations and a PowerPoint presentation that offers a briefing on the report.

An Emergency Management Playbook for State Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
State departments of transportation and other state transportation organizations have many challenges in establishing and maintaining emergency management programs and plans that are proactive, responsive, flexible, and coordinated with the other local, tribal, state, regional, and federal agencies that may be involved in preparedness, mitigation, response and recovery. In addition, states vary in how they organize their emergency management activities. NCHRP Research Report 1093: An Emergency Management Playbook for State Transportation Agencies, from TRB's National Cooperative Highway Research Program, provides information, best practices, and guidelines for ways to 201cwork smart,201d by showing how emergency management can be better organized, understood, and worked into the agency within current resource constraints. Supplemental to the report is NCHRP Web-Only Document 384: Developing an Emergency Response Playbook for State Transportation Agencies, Appendix C: Emergency Management Assistance Compact Guide, a Pocket Guide for Agency Leadership, DOT Mission Ready Packages, Excel Tool for Equipment Comparisons, a Training Materials for Leaders presentation, and a Training Materials for Presenters presentation.

Accelerating Decarbonization in the United States: Technology, Policy, and Societal Dimensions - Transportation Research Board; National Academy of Engineering; National Academy of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Addressing climate change is essential and possible, and it offers a host of benefits - from better public health to new economic opportunities. The United States has a historic opportunity to lead the way in decarbonization by transforming its current energy system to one with net-zero emissions of carbon dioxide. Recent legislation has set the nation on the path to reach its goal of net zero by 2050 in order to avoid the worst consequences of climate change. However, even if implemented as designed, current policy will get the United States only part of the way to its net-zero goal. Accelerating Decarbonization in the United States provides a comprehensive set of actionable recommendations to help policymakers achieve a just and equitable energy transition over the next decade and beyond, including policy, technology, and societal dimensions. This report addresses federal and subnational policy needs to overcome implementation barriers and gaps with a focus on energy justice, workforce development, public health, and public engagement. The report also presents a suite of recommendations for the electricity, transportation, built environment, industrial, fossil fuels, land use, and finance sectors.